NUMBER OF ANGKLUNG DETERMINATION MODEL IN ANGKLUNG ORCHESTRA DISTRIBUTION BASED ON ANGKLUNG SONG ELEMENTS - Aulia Syafiq, Bobi
Angklung is a traditional musical instrument typical of West Java. To play songs with angklung, many angklung and players are needed. Players on angklung teams usually number 25–40 people. Angklung performance with 25–40 players are called angklung orchestra. With the number of angklung and many players needed an arrangement in determining the number of angklung played by the angklung orchestra. This arrangement is called the angklung distribution. One of the criteria for a good angklung distribution is the sound balance of angklung when playing songs. The balance of sound that must be achieved is the clarity of all elements of song composers. In this research, we will discuss about making a model to regulate the ratio of the number of angklung in angklung distribution based on the angklung sound group. Modeling is done by an experimental approach. The model is made by calculating the average intensity of angklung sound for each tone. Next will be determined the average sound intensity of angklung per group. The group is made based on the position of the angklung tone on the song line. The average of the intensity will be compared with the intensity in the song sample to determine the number of angklung. The resulting model is a procedure for determining the amount. Distribution made based on the model has not been better in some aspects compared to conventional models. The advantage of the procedure of this model is that the distributor can estimate the sound produced when the distribution is played. In addition, the distribution generated based on the model can only be applied to certain conditions.